The model of coordinated training for skilled workers and teaching engineers - Michalichenko, A (Professional Pedagogics, 2011)
The model of coordinated training for skilled workers and teaching engineers according to requirements of a labor market is suggested.
Keywords: system of workers training; functional part; providing part; peopleware; quality standards